Effect of three different calcium hydroxide mixtures (calcium hydroxide with glycerine, normal saline and distilled water) on root dentin microhardness - Hasheminia SM; Norouzynasab S (Tehran University of Medical Sciences, 2007)
Background and Aim: During root canal therapy, it is necessary to remove as many bacteria as possible from the root canal. The use of medicaments is recommended to reduce the microbial population prior to root filling. Calcium hydroxide pastes have been used because of their antibacterial effects and the ability of tissue dissolving. The aim of this study was to evaluate the effect of calcium hydroxide/glycerine mixture, calcium hydroxide/normal saline mixture and calcium hydroxide/distilled water mixture on root dentin microhardness in storage times of 7 and 14 days.Materials and Methods: In this in vitro study, fifteen extracted maxillary canines and central incisors were selected. The crowns of the teeth were removed and the canals were prepared. Teeth were sectioned transversally to produce a total of 30 dentin discs from the middle third of the roots. Specimens were divided into three groups of 10 discs each. Dentin samples were subjected to calcium hydroxide/glycerine, calcium hydroxide/normal saline and calcium hydroxide/distilled water mixtures for 7 and 14 days. Dentin microhardness was measured by a Vickers indenter with a load of 200 g for 15 seconds. Data were analyzed using ANOVA, Paired t-test and LSD with p<0.05 as the level of significance.Results: Statistical analysis showed that all three mixtures decreased dentin microhardness. After 7 days, reduction in dentin microhardness by calcium hydroxide/glycerine combination was significantly higher than calcium hydroxide/normal saline and calcium hydroxide/distilled water combinations. After 14 days, reduction in dentin microhardness by calcium hydroxide/distilled water combination was significantly higher than the other two groups.Conclusion: Based on the results of this study, the use of calcium hydroxide combinations for intracanal dressing reduces dentin microhardness. After 7 days calcium hydroxide/glycerine combination and after 14 days calcium hydroxide/distilled water combination are the most effective combinations.